Evaluating Covid-19's impact on firm performance in the carec region using night-time light data: Azerbaijan, Georgia, Kazakhstan, and Mongolia - Kamalbek Karymshakov; Dina Azhgaliyeva; Ranjeeta Mishra; Dastan Aseinov (Asian Development Bank Institute (ADBI), 2022)
This study examines economic activity measured with firm performance indicators using the changes in intensity of night-time light in four CAREC economies: Azerbaijan, Georgia, Kazakhstan, and Mongolia. The empirical analysis is based on the World Bank Enterprise Survey (WBES) data for 2019 and a follow-up survey conducted during the COVID-19 pandemic. The Enterprise Survey dataset was enhanced with data on night-time light intensity from Google Earth and the strictness of "lockdown-style" policies, i.e., the stringency index from Hale et al. (2021). Using the probit regression model, this study investigates the impact of COVID-19 on firm performance and night-time light in CAREC countries. Firm performance is measured using four variables: decrease in sales, demand, export share, and working hours. Our results show that, as the night-time light increases, the likelihood of performance deterioration is reduced. Larger firms are more likely to maintain their performance than smaller firms. The sales in the manufacturing, clothing, and services sectors are more likely to decline than those in the food sector. Accordingly, the results point to a significant decline in the performance of firms operating in the service sector compared with those in the food sector during the pandemic.
Keywords: C55; L25; C13; C25; 330; Central Asia; COVID-19; big data; firm performance; gender; SMEs